2016
DOI: 10.1021/acsami.6b09601
|View full text |Cite
|
Sign up to set email alerts
|

Gel Polymer Electrolytes Containing Anion-Trapping Boron Moieties for Lithium-Ion Battery Applications

Abstract: Gel polymer electrolytes (GPEs) based on semi-interpenetrating polymer network (IPN) structure for lithium-ion batteries were prepared by mixing boron-containing crosslinker (BC) composed of ion-conducting ethylene oxide (EO) chains, crosslinkable methacrylate group, and anion-trapping boron moiety with poly(vinylidene fluoride) (PVDF) followed by ultraviolet light-induced curing process. Various physical and electrochemical properties of the GPEs were systematically investigated by varying the EO chain length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 69 publications
4
70
0
Order By: Relevance
“…As shown in Figure c and 4d, the t Li+ of MBO@PP have increased from 0.24 to 0.57 compared with that of PP separator. It can be concluded that the boron‐oxygen units in MBO acting as Lewis acid sites interacts with Lewis base PF6- , which restricts the migration of PF6- and in turn promotes the migration of Li + , so the t Li+ of MBO@PP increased . Furthermore, the one dimensional fiber structure we introduced to form the coating layer enlarges the contact sites with the anions in the liquid and also could construct an one dimensional Li + conduction pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure c and 4d, the t Li+ of MBO@PP have increased from 0.24 to 0.57 compared with that of PP separator. It can be concluded that the boron‐oxygen units in MBO acting as Lewis acid sites interacts with Lewis base PF6- , which restricts the migration of PF6- and in turn promotes the migration of Li + , so the t Li+ of MBO@PP increased . Furthermore, the one dimensional fiber structure we introduced to form the coating layer enlarges the contact sites with the anions in the liquid and also could construct an one dimensional Li + conduction pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the boron-oxygen units in MBO acting as Lewis acid sites interacts with Lewis base PF À 6 , which restricts the migration of PF À 6 and in turn promotes the migration of Li + , so the t Li + of MBO@PP increased. [20,21,26] Furthermore, the one dimensional fiber structure we introduced to form the coating layer enlarges the contact sites with the anions in the liquid and also could construct an one dimensional Li + conduction pathway. The increase of migration number is beneficial to reduce concentration polarization, especially in the case of high current density, and improve cell performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4-2, for all electrolyte samples, the addition of ETPTA polymer to liquid electrolytes with different salt concentrations does not change the shape of the TFSI -Raman spectrum as they all exhibit two distinct Raman shifts for unbounded and bounded TFSIconfirming that ETPTA polymer does not have any ion-trapping ability [145] and acts merely as an inert polymer. Furthermore, the addition of 1 wt.% glass microfillers to the GPEs at 0.1 and 1 mol·kg -1 LiTFSI shows that the dissociation level of LiTFSI increases as the Raman shift of bounded TFSI -(shoulder ≥ 744 cm -1 ) was significantly reduced.…”
Section: Resultsmentioning
confidence: 77%
“…The appropriate Li + solvation with solvent molecules may increase the favorable accessibility of superoxides to Li + by increasing the salt concentration, which in turn mitigates the electrolyte decomposition [142][143][144]. Gel polymer electrolytes (GPE) consisting of liquid electrolyte and polymer has been successfully used in lithium-ion batteries due to their high ionic conductivity and mechanical stability [91,145,146]. Recently, GPE with different electrolytes and polymers have also been developed for Li-O2 battery applications [61,64,97,98,147].…”
Section: Introductionmentioning
confidence: 99%